Can Pharmacovigilance Data Represent a Potential Tool for Early Detection of the Antibiotic Resistance Phenomenon? - Cecilia Cagnotta; Alessia Zinzi; Francesca Gargano; Valerio Liguori; Maria Rosaria Campitiello; Alessandro Perrella; Annalisa Capuano; Concetta Rafaniello; Ugo Trama (Pharmacoepidemiology)
Background: Antibiotic resistance represents a growing concern. A new strategy developed to treat severe infections is represented by ceftazidime/avibactam (CZA/AVI). Despite the promising activities against more pathogens, continuous monitoring is required to identify potential antibiotic resistance in clinical practice settings. Therefore, real-world data from pharmacovigilance databases can help to better define the safety profile. Methods: We analyzed all Individual Case Safety Reports (ICSRs) collected in the EudraVigilance database focusing on ICSRs with at least one adverse event (AE) potentially suggestive of drug resistance (DR) and drug ineffectiveness (DI). Results: A total of 654 ICSRs related to CZA/AVI were retrieved from EudraVigilance, of which N = 378 (57.8%) were related to male and N = 230 (35.1%) to adult patients. A total of 80.2% of all AEs were serious but with a positive outcome. Overall, we found N = 129 (19.7%) cases of potential DR or DI after CZA/AVI administration. The majority of CZA/AVI-induced DR or DI occurred in adult male patients. The most frequently reported AEs were “drug ineffective” and “pathogen resistance”. Lastly, CZA/AVI was mostly used for the treatment of “Klebsiella infection” and “Pneumonia”. Conclusions: The present study showed how pharmacovigilance could play a key role in generating evidence about the safety profile of CZA/AVI. Further studies are warranted.